Postural Control in Developmental Coordination Disorder and Typical Children: A Systematic Review - Mercê, Cristiana (2018)
Developmental Coordination Disorder (DCD) is a motor disorder without neural compromising that affects 6% of school-age children. One of the most prevalent problems is Postural Control (PC) deficit, which affects 73% to 87% of this population . A systematic review was conducted between 24 February 2016 and 3 March 2016 in order to identify the methodologies formerly used in the PC study on DCD children, and the differences determined between them and typical children with the purpose of identifying clues for a suitable intervention. Article references were searched further for additional relevant publications using the electronic databases: PubMed, Science Direct, Scopus, Web of Science, Cochrane and Scielo. The search was performed in English, French, Portuguese and Spanish. 9 articles were retrieved for analysis, being that no articles mentioning nonlinear methods were found. Previous studies suggest that DCD children are more dependent on visual information (VI). In standing condition DCD children revealed to be more variable and oscillate more than typical, especially with increasing difficulty, e.g. without VI or doing tasks simultaneously. In walking balance with no VI, DCD children significantly decreased their step frequency and step length, walking slower. For a more suitable intervention with DCD children we should: consider attentional factors; work on the perception-action link; work on the timing of gastrocnemius contraction and improve this peak force; moreover, increase the limit of stability in backward excursion.